EXAMINATION BY PROCEDURES AGREED TO THE SALES CYCLE OF THE COMPANY "CLÍNICA ARAUJO" SANTO DOMINGO - García Zambrano, Ximena Leticia; García Zambrano, Ivanna Alexandra; Ferro Ferrín, Galo Enrique; Villalón Peñate, Antonio (mktDESCUBRE, 2020)
The present investigation allowed to evaluate the sales cycle of the “Araujo Clinic”, being a company that is dedicated to both public and private medical care. It began with the collection of information through various methods of data collection such as observation, customer and personal surveys and the interview with the Administrative Manager, results that are presented through tables and graphs Continuing with the study, an internal control questionnaire was applied that allowed us to determine the level of risk globally and for each of the components contemplated by the COSO ERM model and the level of confidence according to the literature; the same that allowed to select the quantity of documents to review in the investigation process. Audit programs were carried out; the same that are expressed in working papers that helped to determine inconsistencies within the organization that were expressed as find-ings contemplated in the final audit report.